Cultivating Collaborative Skills in Elementary School Physical Education Through the Use of Task Constraints. - Kano, Takahiro; Yokoyama, Keiko; Okano, Noboru; Yamamoto, Yuji (JOPERD: The Journal of Physical Education, Recreation & Dance, 2026)
This article explores the cultivation of student collaboration skills in physical education, a vital aspect for individuals to explore their roles in a group and enhance their problem-solving abilities. Traditional approaches have focused mainly on cognitive activities. However, in the approach described here, the source of collaboration with others is physical activity, which consists of the interaction between movement and the environment. Based on cognitive-development and motor-learning research, this article presents a perspective on task constraints for cultivating collaborative skills and proposes a unit (basketball) for physical education classes in elementary schools. Physical education, which enables students to construct meaning through movement, has the potential to support other subjects and activities in education.